Health literacy, eHealth literacy and their association with burden, distress, and self-efficacy among cancer caregivers - Moore, Chloe; Gallagher, Pamela; Dunne, Simon (Frontiers in Psychology, 2024)
Purpose: Health literacy skills are vital for cancer caregivers in helping cancer survivors to navigate their diagnosis, treatment, and recovery but little is known. This study explored health literacy and eHealth literacy among cancer caregivers and the relationship between health literacy/eHealth literacy and potential associated factors.Methods: Informal caregivers who had cared for an individual with cancer completed a survey which collected demographic data and measured caregiver health literacy, eHealth literacy, self-efficacy, burden, and distress.Results: Seven percent of caregivers had inadequate health literacy. Caregivers scored lowest on health literacy domains related to caregiver social support, information seeking and understanding care recipient preferences.eHealth literacy was associated with self-efficacy and burden while, different health literacy domains were associated with burden ('Understanding care recipient needs and preferences'), self-efficacy ('Cancer-related communication with the care recipient' and 'Understanding care recipients needs and preferences') and distress ('Proactivity and determination to seek information', 'Understanding care recipient needs and preferences', 'Understanding the healthcare system').Findings highlight key areas of need regarding cancer caregiver health literacy which future research can target. Given the observed relationship between aspects of health literacy and burden, distress and self-efficacy future work could be carried out on how to alleviate high levels of burden and distress and how to enhance self-efficacy among cancer caregivers by addressing health literacy skills.Findings from this study will inform the development of health literacy interventions to support caregivers to build their health literacy skills and enable this group to better support cancer survivors as a result.